Molecular anthropology: Touching the past through ancient DNA retrieval. Methodological aspects - Witas, Henryk W. (Anthropological Review, 2001)
The revolution which introduced new techniques of molecular biology applied to DNA analysis enormously accelerated the progress in most areas of medicine and biology. Techniques such as polymerase chain reaction (PCR), restriction analysis and sequencing are widely used for diagnosis of a number of diseases, for genetic screening, phylogenetic analysis and population studies. Moreover, it became possible to study genetic relationships of extinct to contemporary organisms and even to follow evolutionary events. Variation in DNA sequences, especially that of humans, is fascinating not only for our own sake, but also because of the inferences that can be drawn from it about our recent evolution, demography and movements. Selected problems arising during ancient DNA (aDNA) isolation and analysis are discussed. Environment and time related factors altering the structure of nucleic acids as well as contamination of isolated material are among methodological problems that arise during the procedure of isolation and processing of aDNA. Resolving them is of great importance for the authentication of the identified sequences. Most common informative targets of aDNA are presented and among them mtDNA, and the sequences localized within nuclear DNA. The first, as well as the most important findings in the field are mentioned.